A State of Underdevelopment: Sovereignty, Nation-Building and Labor in Liberia 1898–1961*. (10th November 2017) - Whyte, Christine
Abstract: In the nineteenth and early twentieth century, Liberia was in the unusual position of being a colony with no metropole. Without military or financial support, the settlers' control over their territory remained weak. Surrounding European empires preyed on this weakness, and Americo-Liberian rule was often at risk from coalitions of European forces and indigenous African resistance. From the early twentieth century, the political elite took on the concept of "development" as a central part of government policy in an attempt to gain political and economic control of the hinterland areas and stave off European incursions. This policy involved the extension and reinforcement of labor policies and practices that had developed through the nineteenth century as means to incorporate settlers and indigenous people into Liberian society. When these plans failed, huge swathes of territory were turned over to foreign commercial interests in an attempt to bolster Liberian claims to sovereignty. And after the Second World War, new policies of "community development" introduced by international agencies again tried to solve Liberia's "land and labor" problem through resettlement. At each stage developmentalist rationales were deployed in order to facilitate greater government control over the Liberian interior territory.